A new possibility for ensuring clean air in farm buildings - Póti, Péter; Vertséné Zándoki, Rita; Kosztolányiné Szentléleki, Andrea; Baschán, Árpád; Pajor, Ferenc (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Stall air may contain various contaminants (gases, dust, microorganisms, viruses) that are harmful for animals and workers. Smallest dust particles (99,99%, respectively. MESP technology can be an ideal solution for defence against contagious diseases in indoor housig systems.
Keywords: air purifying; microelectrostatic precipitation; stall air